Determinants of Inflation in Nepal: An Empirical Assessment - Paudyal, Shoora B. (NRB Economic Review, 2014)
This paper examines short term and long term effects of the macroeconomic variables on the inflation in Nepal during 1975-2011. The variables considered are budget deficits, Indian prices, broad money supply, exchange rate and real GDP. The regression results from Wickens-Breusch Single Equation Error Correction model suggest that all variables considered are significant in long run implying that these variables are the determinants of inflation in Nepal. However, only budget deficit, money supply and Indian prices cause inflation in the short run. The results are consistent with monetarists’ hypothesis of money matters and inflationary gap theory of Keynesian as well as supply constraints approach to inflation.